A COMPREHENSIVE REVIEW ON ACTION OF MRITYUPASACCHEDI GHRITAM IN GARA VISHA - Littija Alex; Ravishankar K; Ashwini Kumar S Bharathi (EPRA International Journal of Research and Development (IJRD), 2022)
Agada tantra is defined as one among the eight branches of Ayurveda which deals with the signs , symptoms and management of poisoning , resulting from the bites of snakes , insects, worms , spiders, rodents etc and various other poisons produced by improper combinations of substances or drugs. Garavisha( concocted poison) is mentioned as a type of visha( poison) which is formed by the combination of two or more poisonous or non-poisonous substances, which slowly gets accumulated in the body and ultimately affects all parts of the body by vitiating all Dosha( humor), Dhatu( tissues), Mala( waste products) and Srotas( channels). Many ayurvedic formulations are mentioned for the treatment of Gara visha. Mrityupasacchedi ghrita is one among them which is explained in Bhaishajya Ratnavali. It is a form of Ghrita Kalpa ( ghee preparation), the use of Ghrita ( ghee) plays an important role in the management of Visha ( poison) condition. It’s effect cures severe poisoning and garadoshaja ( concocted poison) poisoning. It cures disorders like tamaka svasa( bronchial asthma), kandu( itching), mamsasada( depletion of muscles) and visamjna( fainting).It also cures poisoning caused by the bite of snake , poisonous insects , rats and spiders. Mrityupasacchedi ghritam is a formulation that has a combination of many herbs which are easily accessible and have a simple method of preparation . Hence an effort is made to review the Mrityupasacchedi ghritam for Vishahara ( anti-poison) property.